Multilingual Research: Reflections on Translating Qualitative Data. (24th December 2019) - Goitom, Mary
Abstract: The objective of this article is to examine translation dilemmas in cross-cultural qualitative research projects. In particular, I reflect on my experiences of conducting cross-language qualitative research and I examine how the translation techniques I have employed over the years shape the collection and interpretation of non-English to English qualitative data. Centred on the question 'What aspects of participants' representation are lost or foreclosed in this act, process and outcome of translating and how can this be mitigated?', I discuss how the following coalesce to inform how this complex and multidimensional question is addressed: (i) the competencies, processes and outcomes of translating, (ii) the importance of situating data in its social context and (iii) how this shapes the representation of data. As well, this article discusses the implication of cross-cultural and cross-language studies on social work and presents three lessons learned from my experiences.